Developing decentralized business within highly institutionally centralized environment: the case of blockchain-based business in China - Zhu, Xiaoqing (My University, 2022)
Blockchain-based business and therefore cryptocurrency-related activities are spreading globally developing the newly emerging crypto economy. However, regulatory responses to the crypto economy and businesses within it were very diverse in different countries. Given the above, the main research aim was to investigate how blockchain-based business (BBB) with idea of opposing the institutional regulations can be developed in the regula-tory adverse institutional environment. More specifically, this thesis investigated, how BBB are developed within the ultimate institutional constrains in the environment, such as China, where crypto-related activities are banned. The research question for the thesis was how to develop decentralized BBB in highly centralized institutional environment of China? The research objectives were to assess blockchain technology's impact on Chinese companies; to explore the situation of BBB in China; and to explore how companies in BBB in China cope with the institutional environment. The case study approach was undertaken for this research. Qualitative semi-structured interviews were conducted with six interviews, leaders of successful BBB in China. To sup-port primary data, secondary data was collected to deeper learn about the BBB cases in-vestigated. The findings suggest that strict institutional environment for BBB in China has a significant impact on BBB innovation and growth in several diverse ways. On the one hand, the Chi-nese government is promoting blockchain technology and innovations related to it. On the other hand, the cryptocurrency, as one of the most prominent blockchain technology application, is a contentious issue that the Chinese government opposes. As a result, the Chinese government considers BBB regulation to be necessary and essential. Firms that are operating in Chinese market do not necessarily need to stop their operations and de-velopment of the BBB. However, they need to make various adjustments to balance out the requirements of the regulatory regime. The thesis contributes to the literature by showcasing how innovative decentralized busi-nesses, such as BBB can remain active within adverse and regulatory pressing institutional environment.
Keywords: People's Republic of China; blockchains; enterprises; virtual currency; business environment; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development